Dual mode acoustic wave sensor for precise pressure reading - Mu, Xiaojing (2015)
In this letter, a Microelectromechanical system acoustic wave sensor, which has a dual mode (lateral field exited Lamb wave mode and surface acoustic wave (SAW) mode) behavior, is presented for precious pressure change read out. Comb-like interdigital structured electrodes on top of piezoelectric material aluminium nitride (AlN) are used to generate the wave modes. The sensor membrane consists of single crystalline silicon formed by backside-etching of the bulk material of a silicon on insulator wafer having variable device thickness layer (5 μm–50 μm). With this principle, a pressure sensor has been fabricated and mounted on a pressure test package with pressure applied to the backside of the membrane within a range of 0 psi to 300 psi. The temperature coefficient of frequency was experimentally measured in the temperature range of −50 °C to 300 °C. This idea demonstrates a piezoelectric based sensor having two modes SAW/Lamb wave for direct physical parameter—pressure readout and temperature cancellation which can operate in harsh environment such as oil and gas exploration, automobile and aeronautic applications using the dual mode behavior of the sensor and differential readout at the same time.